Development of an Interdisciplinary Blended Learning Module for Postgraduate Research Methodology Course - Rahim R.E.A.; Der C.S.; Din N.M. (Association for Computing Machinery, 2023)
Computer aided instruction; Curricula; E-learning; Education computing; Electronic commerce; Academic institutions; Blended learning; Flexible Learning; Innovative learning; Instructional designs; Post-graduate levels; Post-graduate research; Research methodologies; Learning systems